Rancang Bangun Dashboard Business Intelligence untuk Monitoring Kinerja Penjualan Queen Cell - Akhmadi Wirawan; Elita Yuni Setiyarini (Jurnal Multidisiplin Indonesia, 2026)
Advancements in information technology encourage business owners to leverage data as a foundation for more effective and accurate decision-making. Queen Cell is a business specializing in the sale of mobile phones and accessories, generating daily sales transaction data. However, sales information is currently presented using conventional methods, complicating performance monitoring and sales evaluation. This study aims to design a Business Intelligence dashboard for monitoring Queen Cell’s sales performance, capable of presenting sales data in a visual, interactive, and easily understandable format to support decision-making. The research employs the Research and Development (R&D) method, encompassing stages such as needs identification, data collection, requirements analysis, interface design, prototype creation using the Figma platform, and evaluation and validation. The dashboard is designed to display Key Performance Indicators (KPIs), including total profit, total revenue, units sold, average margin, sales trends, profit composition by product category, and profit comparison per product. Evaluation results indicate that the dashboard prototype achieved a feasibility score of 95% (classified as "Highly Feasible"), thereby satisfying criteria regarding ease of use, visual quality, information clarity, and alignment with user needs. The resulting dashboard presents sales information in a structured and informative manner, enabling the Queen Cell owner to monitor sales performance, evaluate business operations, and support decision-making that is effective, efficient, and data-driven. This prototype is expected to serve as a reference for the development of the Business Intelligence system during the implementation phase.